Screening key sorghum germplasms for low-nitrogen tolerance at the seedling stage and identifying from the carbon and nitrogen metabolism - Liu, Chunjuan; Gu, Wendong; Li, Bang; Feng, Yihao; Liu, Chang; Shi, Xiaolong; Zhou, Yufei (Frontiers in Plant Science, 2024)
Sorghum (Sorghum bicolor L.) can withstand drought and heat stress and efficiently utilize water and nutrients. However, the underlying mechanism of its tolerance to low-nitrogen (N) stress remains poorly understood. This study assessed low-N tolerance in 100 sorghum-inbred lines and identified those with exceptional resilience. Principal component analysis, Pearson’s correlation, and Y-value analysis were used to examine various seedling growth metrics, including plant and root dimensions, biomass, chlorophyll content, root N content, shoot N content, and root/shoot ratio. The genotypes were categorized into four distinct groups based on their respective Y values, revealing a spectrum from highly tolerant to sensitive. Low-N-tolerant sorghum lines maintained higher photosynthetic rates and exhibited increased enzymatic activities linked to carbon and N metabolism in the leaves and roots. Furthermore, low-N-tolerant genotypes had higher levels of key amino acids, including cystine, glycine, histidine, isoleucine, leucine, phenylalanine, threonine, and tyrosine, indicating a robust internal metabolic response to N deficiency. This study provides a comprehensive and reliable approach for the evaluation of sorghum tolerance to low-N environments, sheds light on its morphological and physiological adaptations, and provides valuable insights for future breeding programs and agricultural practices.